8(y+4)=2(3y+4)

Simple and best practice solution for 8(y+4)=2(3y+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(y+4)=2(3y+4) equation:


Simplifying
8(y + 4) = 2(3y + 4)

Reorder the terms:
8(4 + y) = 2(3y + 4)
(4 * 8 + y * 8) = 2(3y + 4)
(32 + 8y) = 2(3y + 4)

Reorder the terms:
32 + 8y = 2(4 + 3y)
32 + 8y = (4 * 2 + 3y * 2)
32 + 8y = (8 + 6y)

Solving
32 + 8y = 8 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
32 + 8y + -6y = 8 + 6y + -6y

Combine like terms: 8y + -6y = 2y
32 + 2y = 8 + 6y + -6y

Combine like terms: 6y + -6y = 0
32 + 2y = 8 + 0
32 + 2y = 8

Add '-32' to each side of the equation.
32 + -32 + 2y = 8 + -32

Combine like terms: 32 + -32 = 0
0 + 2y = 8 + -32
2y = 8 + -32

Combine like terms: 8 + -32 = -24
2y = -24

Divide each side by '2'.
y = -12

Simplifying
y = -12

 

See similar equations:

| 6/510/7= | | 3(2-x)-8(9-4x)=7+3(x-4) | | 90+90+x+x+22+x+22+x=720 | | M-4-3=7 | | 4x-11=4+5 | | 110+130+x+x-3=360 | | 84-(6x+15)=6(x+5)+x | | -4-8n=-4(8+4n)+4 | | 15.9x-45+4x-16=4 | | 0.5(7x+14)=1.4-(x+2) | | 4r^2-11r-3=0 | | 6x^2-7+2x= | | -(8+2x)=-40-6x | | 1.8+9=-5.7x-6 | | -4+1/2z=-5 | | 5-8(4p+7)=173 | | y^2=36y | | 4x+6-2x=4(x+3) | | Y=135-2x | | 9x+3y=21 | | 8x-8/4=5-3x | | -8(x-3)-5=19 | | 19.9=-8 | | 3x+2x=6p+4-2 | | z-4/9=-2 | | 5x+7=4+2x+17 | | 0=-16x^2+1156 | | x^2-6x+112=0 | | -108=-6b | | 4x+3=-7+2x+14 | | 3x+3y=5 | | y/4=56 | | 54=3u | | -3(t-1)+5t=9t-4 | | 42=v/2 | | 4/7m=18-2/7m | | 10+(3/5)x=4 | | 50=x+4x+5 | | 5(y+9)+y=3(y+4)+6 | | 16=x-(-14) | | t(7-2)=9*7-9*2 | | 10x^6-45x^5+45x^4= | | 12w4-6w3+w2/3w2 | | 38x-42=5(7x-9)+3x+3 | | (2/5)v-3=(v/2) | | 9(3n+1)=8(8n+8)+8 | | x^2-x+670=0 | | 6w=84 | | x^2-x-670=0 | | 5(x-3)+4=3x+2(-3+x) | | -7x-17=2x+10 | | x^3+y^3=2011 | | 9n-3(5-2n)= | | 12x^2=27x-15 | | 3(7.5)+14= | | 9=n-8 | | 2/5x+4/5=-2/5 | | y=3(-7.5)+14 | | 1=7-r | | 7n-18=31 | | 4x-12=x+5 | | x^3-y^3=2011 | | (x+1/3)-(x-2/4)=5/6 | | 4(2x-5)=-28 | | wy+5w-7y-35= |